An Evaluation of Nutritional Factors on The Prevalence of Urolithiasis in Cats at The Veterinary Teaching Hospital, Universitas Airlangga During 2017-2019 - Mahdi, Daffa Amanul; Sardjana, I Komang Wiarsa; Yudaniayanti, Ira Sari; Estoepangestie, Agnes Theresia Soelih; Triakoso, Nusdianto; Primarizky, Hardany (Jurnal Medik Veteriner, 2023)
Stones, or uroliths, in the urinary tract cause a disorder called urolithiasis. Patients with urolithiasis may experience blockage and possibly mortality; therefore, prompt treatment is imperative. This study aimed to investigate the prevalence of urolithiasis and its nutritional association in cats treated at the Veterinary Teaching Hospital, Universitas Airlangga during 2017-2019. Data was collected from the secondary resource from the medical report and the factor of feed nutrition involved fiber, protein, fat, and moisture. Data was analyzed using logistic regression to determine the influence of nutrition on the prevalence of urolithiasis in cats in the respective period. The findings indicated that in 2017, urolithiasis prevalence was 0,96%; in 2018, it was 5,55%; and in 2019, it was 0,91%. Meanwhile, it was revealed that the prevalence of urolithiasis was not significantly impacted by feed nutritional variables.